2015
DOI: 10.1007/s00264-015-3044-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of percutaneous trephine excision and open surgery in the treatment of osteoid osteoma

Abstract: Percutaneous excision with trephine is a more successful, effective, minimally invasive, safe and a better cosmetic approach in the treatment of osteoid osteoma. This method is also a cheap method that does not require expensive equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Thus during operation only minimal cortical bone had to be removed to allow total excision of the nidus after localizing the site & its surrounding a multiple drill holes using 3.5 drill pit was done to facilitate total resection by hummer &osteotom. .We do not use any other methods of localizing nidus such as pre-operative injection of technetium 99 methylene diphosphonate and intra-operativeprobing, or injecting tetracycline pre-operatively and examining the specimen under ultraviolet light are necessary (14,15) .Xiaoning et al(N=14) (16) had concluded that conventional excision surgery of ostoidosteoma was effective and safe treatment, associated with a low local recurrence and complication rate.This is also confirm by Lin et al (N=14) who had concluded that the niduses of osteoid osteomas can be eradicated by open surgery with 3-D C-arm scan under the guidance of computer navigation with minimal damage to bone structure and a high rate of pathologically confirmed diagnoses. (17) Al qurashi et al (N=12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus during operation only minimal cortical bone had to be removed to allow total excision of the nidus after localizing the site & its surrounding a multiple drill holes using 3.5 drill pit was done to facilitate total resection by hummer &osteotom. .We do not use any other methods of localizing nidus such as pre-operative injection of technetium 99 methylene diphosphonate and intra-operativeprobing, or injecting tetracycline pre-operatively and examining the specimen under ultraviolet light are necessary (14,15) .Xiaoning et al(N=14) (16) had concluded that conventional excision surgery of ostoidosteoma was effective and safe treatment, associated with a low local recurrence and complication rate.This is also confirm by Lin et al (N=14) who had concluded that the niduses of osteoid osteomas can be eradicated by open surgery with 3-D C-arm scan under the guidance of computer navigation with minimal damage to bone structure and a high rate of pathologically confirmed diagnoses. (17) Al qurashi et al (N=12).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, surgical resection has been the next step and was the definitive treatment for a long time. 15 But open surgery may result in procedure-related complications and a long hospital stay. 16 Recently, RFA has been applied more diffusely in the treatment of osteoid osteoma owing to fewer complications and shorter length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the main treatments for osteoid osteoma are conventional open surgery, CT‐guided radiofrequency ablation and computer navigation‐guided open surgery. Compared with open surgery, CT‐guided radiofrequency ablation has the advantages of less operative trauma and more accurate localization of the nidus. However, its drawbacks include difficulty in precise control of the radiofrequency dosage and inability to detect damage intra‐operatively, which leads to failure to relieve symptoms in some patients.…”
Section: Discussionmentioning
confidence: 99%